Kadar Serat dan Kadar Air serta Penampakan Fisik Produk Pascapanen Daun Caisim (Brassica juncea L.) yang Ditanam pada Media dengan Penambahan Pupuk Organik Hayati Cair dan Pupuk Anorganik - Winarsih, Dwi; Prihastanti, Erma; Saptiningsih, Endang (Bioma : Berkala Ilmiah Biologi, 2012)
Caisim (Brassica juncea L.) is one of vegetable commodities that has a high commercial value. Many people like it because it has a good taste and it contains several kinds of vitamin and mineral that good for health. This research aims to know the influence of liquid bio organic fertilizer and inorganic fertilizer addition to post harvest product caisim leaf and know the best combination of fertilizer for post harvest product caisim leafquality. Data analysis used is Analysis of Variance (ANOVA) and then continued by test significant different used Duncan Multiple Range Test (DMRT) 95%. The caisim plant that have been harvested then being observed on its fiber content, water content, and physical appearance. The result showed thatthe addition of liquid bio organic fertilizer and inorganic fertilizer has not influence for water content and physical appearance of caisim leaf, but it has an influence on fiber content. Treatment with basic media with the addition of 1 mL + 2,17 g NPK is the best treatment to increase fiber content of caisim leaf Tosakan variety. Â  Keywords: liquid bio organic fertilizer, caisim, quality of post harvest product